Bioremediation efficiency of the largest scale artificial Porphyra yezoensis cultivation in the open sea in China. Issue 1 (15th June 2015) - Wu, Hailong; Huo, Yuanzi; Zhang, Jianheng; Liu, Yuanyuan; Zhao, Yating; He, Peimin
Highlights: The study area is China's largest Porphyra yezoensis aquaculture areas. The bioremediation efficiency of Porphyra yezoensis cultivation was determined. The ability of nutrients removal and harmful algae bloom control was studied. Abstract: The bioremediation efficiency of China's largest scale Porphyra yezoensis cultivation for removing dissolved nutrients and controlling harmful algae was studied in the radial sandbanks waters of Jiangsu Province in the year 2012–2013. Mean nutrient concentration values in the P. yezoensis cultivation area were significantly lower than those in the non-cultivation area, especially during the cultivation season ( p < 0.05). Tissue nitrogen and phosphorus contents of seaweeds were 5.99–0.80% (dry weight (DW)) and 0.16–0.19% (DW), respectively. Production of P. yezoensis was 58950.87 tons DW. Based on these values, 3688.15 tons of tissue nitrogen and 105.61 tons of tissue phosphorus were removed by harvesting P. yezoensis . The richness index of the red tide species Skeleton emacostatum declined from 0.32 to 0.05 during the P. yezoensis cultivation season. These results indicate that large-scale cultivation of P. yezoensis can be used to efficiently alleviate eutrophication and control harmful algae blooms in open sea.